Intraepithelial and Lamina Propria Lymphocytes Do Not Correlate With Symptoms or Exposures in Microscopic Colitis. Issue 3 (10th March 2022) - Sandler, Robert S.; Hansen, Jonathan J.; Peery, Anne F.; Woosley, John T.; Galanko, Joseph A.; Keku, Temitope O.
Abstract : INTRODUCTION: Microscopic colitis, a common cause of diarrhea, is characterized by a largely normal appearance of the mucosa but increased numbers of lymphocytes in the epithelium and lamina propria on microscopy. We sought to determine whether T-cell percentage was associated with exposures or symptoms. METHODS: We conducted a case-control study that enrolled patients referred for colonoscopy for diarrhea. Patients were classified as microscopic colitis cases or controls by an experienced pathologist. Participants provided information on symptoms and exposures during a telephone or internet survey. Research biopsies from the ascending colon and descending colon were examined using immunofluorescence stains for CD3, CD8, and FOXP3 to determine percent T cells per total epithelial or lamina propria cells. Digital images were analyzed by regions of interest using Tissue Studio. RESULTS: There were 97 microscopic colitis cases and 165 diarrhea controls. There was no association between demographic factors and percentage of intraepithelial or lamina propria T cells. In cases, the mean percent T cells were similar in the right colon and left colon. There was no association between mean percent T cells and stool frequency or consistency. There was no association with irritable bowel syndrome, abdominal pain, or medications purported to cause microscopic colitis. DISCUSSION: The lack of association between the density of T cells and medications raises further doubts about their role in disease etiology. Loose and frequent stools in patients with microscopic colitis are not correlated with T-cell density.